Application of Virtual Private Network Technology in Computer Network Information Security - Yu, Jihao; Song, Yi (Journal of Theory and Practice of Engineering Science, 2025)
With the continuous development of China's social economy, the pace of scientific and technological advancement in our country has been accelerating. Internet technology and computer technology have been expanding rapidly in the course of technological development. However, as the information age progresses, the issue of information security in internet technology has become increasingly important. In the realm of the internet, people's online information faces numerous threats, making it essential to maintain the security of internet information. This paper discusses the application of Virtual Private Network (VPN) technology in computer network information security, providing an overview of VPN technology in the hope of assisting relevant technical personnel.